Testing corn flour - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The first tests for producing corn flour at the industrial level in Senegal have been completed. The initial 300 kg of macaroni made with a 50/50 or 70/30 blend of wheat and corn flour were considered quite acceptable. Taste and marketing trials...